Avaliação da produção de peptídeos antifúngicos (PAFs) expressos por fungos do gênero penicillium e aspergillus - Wilkon, Nickson Willian Vedigal (2024)
The emergence of new fungal diseases has become a global public health issue. In recent years, the search for new sources of bioactives capable of being applied against pathogenic fungi in humans and for the control of phytopathogens has accelerated. In this context, antifungal peptides (AFPs) are stable molecules considered promising as new effective antifungals to target fungi resistant to current antifungal treatments. The fungi for the study were selected based on a review of the literature and genomic database analyses. The fungi Penicillium expansum, Penicillium citrinum, and Aspergillus flavus were selected, as they are reported producers of AFPs. The fungi were identified through sequencing of the ribosomal DNA gene region via conventional PCR amplification using the ITS1 and ITS4 primers described in the literature. The fungal genomic DNA was extracted and purified with phenol-chloroform, and after quantification and visualization of DNA integrity on agarose gel, PCR was performed in our laboratory, and sequencing was carried out by Ludwig Biotechnology. The obtained sequences were analyzed using BLASTn, and after fungal identification through phylogenetic analysis, the sequences were deposited in GenBank. A hypothetical antifungal peptide from Aspergillus flavus was found in the Ensembl Fungi database, and primers were designed using the OligoAnalyzer tool (Integrated DNA Technologies-IDT) to amplify the gene encoding this AFP. The three-dimensional structure of the antifungal peptide was initially modeled using templates from the Swiss-Model database. Primers for three classes of AFPs previously described in the literature were synthesized and initially used in PCR with the genomic DNA of P. citrinum for reaction optimization. However, despite amplification in P. expansum, P. citrinum, and A. flavus, the sequenced amplicons did not correspond to AFP genes. The fungi were cultured in liquid medium under agitation and stationary conditions, as described in the literature. Antifungal activity assays were conducted in 96-well plates using culture extract samples purified through molecular exclusion chromatography. Sensitivity tests revealed that Aspergillus niger was susceptible to extracts produced by P. citrinum and A. flavus. Specifically, P. citrinum sample A2 and A. flavus samples A1, A2, A5, A6, G1, G6, G7, H1, H4, H5, and H8 exhibited antifungal activity. The fractions of the purified liquid culture extracts were quantified and subjected to electrophoresis using 16% Tricine SDS-PAGE, revealing the presence of peptides. However, these peptides were not characterized in this study, paving the way for future biochemical characterization of the peptides present in the extracts.